Midwives' Psychosocial Experiences in Pregnancy and Childbirth Services During The Covid-19 Pandemic - Shelly Rodliah Rosyad; Andari Wuri Astuti; Asri Hidayat (Universitas Aisyah Pringsewu, 2022)
The safety aspect of health workers including midwives as the frontline in handling patients during the COVID-19 pandemic is at risk of being very vulnerable to being exposed to COVID-19 which threatens their lives and safety. Physical and mental fatigue in health workers during a pandemic increases the risk of burnout which can reduce the quality of service to patients. The purpose of this study was to review evidence related to the psychosocial experience of midwives in pregnancy and childbirth services during the COVID-19 pandemic. The method used was a scoping review beginning with the identification of scoping review questions using the PEO framework; identifying relevant articles to be determined based on inclusion and exclusion criteria; searching for articles using databases, namely Proquest, PubMed, Science Direct, and Wiley Online Library; selecting articles whose search flow is described through the PRISMA Flowchart; performing data charting and critical appraisal; compiling and reporting results. The results obtained based on 8 articles that had been critically appraised showed that 6 articles used qualitative studies, 1 article used mixed-method quantitative study, and 1 article used quantitative descriptive study. A total of 3 themes emerged, namely about the psychological impact, challenges and needs of midwives in pregnancy and childbirth services during the COVID-19 pandemic which affected the experience felt by midwives in pregnancy and childbirth services with psychological impacts such as fear and burnout. In addition, there were challenges faced by midwives and things that were needed by midwives in pregnancy and childbirth services during the COVID-19 pandemic. Abstrak: Aspek keselamatan tenaga kesehatan termasuk bidan sebagai garda terdepan dalam menangani pasien selama pandemic COVID-19 berisiko sangat rentan untuk terpapar COVID-19 yang mengancam jiwa dan keselamatannya. Kelelahan fisik dan mental pada tenaga kesehatan di masa pandemic meningkatkan resiko terjadinya burnout yang dapat mengurangi kualitas dalam pelayanan pada pasien. Tujuan penelitian ini untuk mereview evidence terkait dengan pengalaman psikososial bidan dalam pelayanan kehamilan dan persalinan di masa pandemic COVID-19. Metode yang digunakan ialah scoping review diawali dengan identifikasi pertanyaan scoping review menggunakan framework PEO; mengidentifikasi artikel yang relevan dengan ditentukan berdasarkan kriteria inklusi dan eksklusi; melakukan pencarian artikel menggunakan database yakni Proquest, PubMed, Science Direct, dan Wiley Online Library; melakukan seleksi artikel yang alur pencariannya digambarkan melalui PRISMA Flowchart; melakukan data charting dan critical appraisal; menyusun dan melaporkan hasil. Hasil yang diperoleh berdasarkan 8 artikel yang telah dilakukan critical appraisal, sebanyak 6 artikel menggunakan studi kualitatif, 1 artikel menggunakan kuantitatif mixed-method, dan 1 artikel menggunakan studi deskriptif kuantitatif. Sebanyak 3 tema yang muncul yakni tentang dampak psikologis, tantangan dan kebutuhan bidan dalam pelayanan kehamilan dan persalinan dimasa pandemic COVID-19 yang mempengaruhi pengalaman yang dirasakan oleh bidan dalam pelayanan kehamilan dan persalinan dengan adanya dampak psikologis seperti ketakutan dan burnout. Selain itu terdapat tantangan yang dihadapi oleh bidan dan hal-hal yang menjadi kebutuhan bidan dalam pelayanan kehamilan dan persalinan di masa pandemic COVID-19.